2022
DOI: 10.1128/mbio.01166-22
|View full text |Cite
|
Sign up to set email alerts
|

Human FcRn Is a Two-in-One Attachment-Uncoating Receptor for Echovirus 18

Abstract: E18 is a member of enterovirus species B. As one of the most common enterovirus serotypes in nonpolio enterovirus detection, it easily infects children and causes various clinical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…This finding is in alignment with our previous observation, that both ZIKV and its envelope glycoprotein E can enter and passage through MDCK/FcRn cells at higher levels than MDCK/vector cells [12]. It is possible that E protein interacts directly with FcRn, as has been reported for other viruses [21,22]; however, our binding studies to detect direct interaction of purified envelope glycoprotein and FcRn did not yield positive results (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in alignment with our previous observation, that both ZIKV and its envelope glycoprotein E can enter and passage through MDCK/FcRn cells at higher levels than MDCK/vector cells [12]. It is possible that E protein interacts directly with FcRn, as has been reported for other viruses [21,22]; however, our binding studies to detect direct interaction of purified envelope glycoprotein and FcRn did not yield positive results (data not shown).…”
Section: Discussionsupporting
confidence: 92%
“…Human FcRn has been demonstrated to be a two-in-one attachment-uncoating receptor of E18, and we hypothesize that this receptor plays a similar role in E30 invasion, because siRNA knockdown of DAF alone does not prevent E30 invasion, but siRNA treatment of FcRn completely abolishes E30 infection, as previously mentioned (Vandesande et al, 2020;Chen et al, 2022). Although FcRn plays an important role in E30 viral decapitation and is a necessary receptor for E30 invasion, studies have demonstrated that human FcRn expression is insufficient to infect echovirus through an in vivo pathway of the gastrointestinal tract; Type I IFN is a major driver of echovirus transmission from the gastrointestinal tract to secondary sites, including the liver and pancreas; and Type III IFN inhibits persistent echovirus infection in gastrointestinal epithelial cells (Wells et al, 2021(Wells et al, , 2022.…”
Section: Downstream Pathwayssupporting
confidence: 54%
“…Indeed, our screening results paralleled a recent report identifying critical host factors for echovirus 6, in which FCGRT, CD55, and B2M emerged as the top three hits 17 . While CD55 serves as a critical receptor for echovirus attachment 29 , FcRn is involved in echovirus uncoating and genome release 17,30 . HAstV may share similar entry mechanisms, with DPP4 replacing the activity of CD55.…”
Section: Pharmacological Inhibition Of Fcrn or Dpp4 Prevents Hastv In...mentioning
confidence: 99%